The Key Areas Turkey Needs to Work on Due to Improve Entrepreneurship - Senay Oguztimur (European Regional Science Association (ERSA), 2014)
Even though Turkey is frequently regarded as an emerging market and actually has many advantages to be considered as an attractive place to invest and do business, it is not that much attractive for international economy world. Despite Turkey's capacity, such as being 16th largest market with its young population as well as approximately 8% gross domestic product increase, varied industry base with a wide talent pool, according to various international independent research institutes, the global market does not view Turkey as a beneficial place for entrepreneurship. Moreover there are quite a large number of barriers to attract investment and to make successful investment and entrepreneurship opportunities in Turkey. Besides the entrepreneurship indicators in Turkey demonstrate similar point. One of the most conspicuous is that just about six tenth of Turkish people regard their local environment to be a good one for fostering entrepreneurs and entrepreneurship. The very little number of female entrepreneurs (while compared with the man-dominant market) is also a barrier to Turkey becoming a positive and inclusive environment for continued entrepreneurial growth. With consideration paid to given statistics in recent years, Turkey generally remains in the last quarter while compared with the overall countries having possibility to attract entrepreneurs. After analyzing the present circumstances, this paper focuses on the national and local level of obstacles of entrepreneurship in Turkey. Within the light of the researches of statistics and secondary documents; it is obvious that Turkey should take into account such the following issues: chaos in Turkish bureaucracy, counterworks in protecting intellectual property and drawbacks to break monopolies in the marketplace are the first significant points to worth stressing. To support entrepreneurship, reforms and regulations need to be done in order to create an inviting and successful atmosphere for potential entrepreneurs even from local level and from international market. In order to deal with the problems of enlargement the capacity of Turkish entrepreneurship, commitment to fostering a positive environment for entrepreneurship should have done over and above launching a series of programs designed to foster growth and support entrepreneurship. The main purpose of this paper is to evaluate the key points that Turkey needs to work on due to improve entrepreneurship.
Keywords: L26; 330